The impact of the brazilian college admissions exam on the perceived stress of young adult - Maia, Maria Nogueira; Caldas, Roseli (Seven Editora, 2023)
The first standardized selection instrument for university admission in Brazil was defined by Decree 8.659 on October 5, 1911. It approved the Organic Law of Higher and Fundamental Education - also known as the Rivadávia Corrêa Reform - establishing: "To be granted enrollment, the candidate will undergo an examination that enables an overall assessment of their intellectual development and capacity to effectively undertake the study of the subjects that constitute the college curriculum." (RIBEIRO NETO, 1985, p. 41). It consisted of an oral examination of languages and sciences, as well as a written section in Portuguese that covered specific content. DOI:https://doi.org/10.56238/ptoketheeducati-059